Evolution and Trends of Indexes of Reliability in Electrical Systems of Power - Gómez-Ramírez, Gustavo Adolfo (2016)
The basic function of a system of power consists of the supply of electric power to the clients, economic, efficient form, and to provide an effective service. Nevertheless, there exist certain restrictions that they affect considerably in order that such a situation is fulfilled. Some of them, they are related directly to the quality of service, between that we can mention: Variations in tension of bars and of the industrial frequency. These problems have been taken in consideration by designers, gliders and operators of the electrical systems of power. Many of the technologies that have been developed by a lot of time are to attend and to solve the dilemma, in spite of the economic limitations of operation and maintenance. The indexes of reliability are a sample of them, so across the time, have been designed, in order to quantify the events related so much in his operation, as the conditions of maintenance, faults, between others in the diverse periods of the year, especially for the affectation to the clients and first of all the economic losses that can produce. In the following technical note the evolution is analyzed of these in the time and the diverse technologies are explained for the analysis. Likewise there develops an example applied to a system of electrical power.